Firm Value: Carbon Emissions Disclosure, Profitability And Audit Committee - Nurbaiti, Annisa; Rahayu, Meidina Putri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The aim of this study is to examine how carbon emissions disclosure, profitability, and audit committee effect firm value on Energy, Raw Materials, Industry, Consumer Cyclicals and Consumer Non-Cyclicals Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2021. In this study, multiple linear regression analysis was performed on data from 223 different companies. The findings demonstrated that the variables of carbon emissions disclosure, profitability and audit committee had effect on firm value. Partially, Profitability has effect on firm value, and it means profitability more important than the disclosure of carbon emissions or the presence of an audit committee determining the stock price. This indicates that the level of profitability, as measured by ROA, might be a factor in the increase in the company's value.